Evaluating the impact of a virtual educational intervention on medical students' knowledge and attitudes towards patients with intellectual and developmental disabilities. Issue 1 (2nd January 2023) - Berger, I.; Weissman, S.; Raheel, H.; Bagga, A.; Wright, R.; Leung, F.; Loh, A.; Lee-Jones, C.; Isaacs, B.; Vogt, J.
ABSTRACT: Background: Research suggests physicians may harbour paternalistic attitudes towards people with intellectual and developmental disabilities and lack the knowledge and skills to work with them. This study examined the impact of a brief intellectual and developmental disability curriculum intervention on these outcomes. Methods: First-year medical students completed a pre–post questionnaire on attitudes and knowledge of intellectual and developmental disabilities in conjunction with a curriculum (a virtual tour of a developmental service site; panel discussions; tutorial presentations). Paired data were available for 33 students. Results: Students' confidence communicating with the person increased (pre-mean = 5.7/10, SD = 1.9; post-mean = 6.3/10, SD = 1.7; p < 0.05) as did their feeling of competence taking a history (pre-mean = 4.2/10, SD = 1.9; post-mean = 5.5, SD = 1.7; p < 0.0001). Their inclination toward sheltering people with intellectual and developmental disabilities also increased (pre-mean = 2.8/6, SD = 0.7; post-mean = 3.2/6, SD = 0.7; p < 0.005). Conclusion: This intervention may contribute to student confidence and their sense of competence in interacting with people with intellectual and developmental disabilities but did not suggest they adopted the philosophy of community inclusion.